2002
DOI: 10.1002/clc.4960251004
|View full text |Cite
|
Sign up to set email alerts
|

C‐reactive protein as a marker for active coronary artery disease in patients with chest pain in the emergency room

Abstract: SummaryBackground: Markers of inflammation, such as C-reactive protein (CRP), were found to be related to risk for cardiovascular disease (CVD) events in patients with angina pectoris. In addition, recent studies have shown that, in the case of atherosclerosis, increased CRP concentration reflects the inflammatory condition of the vascular wall.Hypothesis: The study was undertaken to determine whether CRP levels in individuals with chest pain attending the emergency room (ER) may be used as a marker of active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 30 publications
(24 reference statements)
2
9
1
Order By: Relevance
“…Such data suggest that CRP level on admission may be a ACS marker to identify patients at higher risk of developing AMI 20 . Higher CRP level in the group of patients with ACS compared with the other patients experiencing chest pain was also found in another study 21 .…”
Section: Potsch E Cols C-reactive Protein Diagnostic and Prognostic supporting
confidence: 72%
“…Such data suggest that CRP level on admission may be a ACS marker to identify patients at higher risk of developing AMI 20 . Higher CRP level in the group of patients with ACS compared with the other patients experiencing chest pain was also found in another study 21 .…”
Section: Potsch E Cols C-reactive Protein Diagnostic and Prognostic supporting
confidence: 72%
“…Simultaneously, patients presenting with elevated troponins have an increased risk of more serious ischemic complications during short- and long-term follow-up [31]. A more or less similar situation exists with regard to C-reactive protein, a marker of inflammation [32, 33], and brain natriuretic peptide, a circulating cardiac hormone [34]. Our data fit nicely with this development, as the vectorcardiographic variables under investigation had both diagnostic and prognostic impact.…”
Section: Discussionsupporting
confidence: 69%
“…Lindmark et al [ 27 ] have tested this hypothesis in patients with unstable coronary artery disease and found that high circulating IL-6 identifies patients who benefit most from a strategy of early invasive management. Differently than IL-6, hs-CRP has a strong negative predictive value in patients with chest pain in the emergency room [ 28 ]. Testing the combination of these two inflammatory markers could bring interesting results.…”
Section: Discussionmentioning
confidence: 99%